Organizational-Technological Modeling In The Reconstruction Of Higher Education Institution Buildings - Yernazarova, Gulnaz Puxarbayevna; Fayzulloeva, Maftuna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
The reconstruction of higher education institution buildings represents a critical challenge in modern educational infrastructure development, requiring sophisticated organizational-technological approaches to ensure minimal disruption to academic activities while achieving optimal renovation outcomes.